Assistance in Strengthening Governance and Management of Bahtera Beach Tourism Services - Erinaldi Erinaldi; Fitra Hadi Khaz; Keke Ananta (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This Community Service Program (PkM) was motivated by the suboptimal organizational governance and tourism service management at Bahtera Beach. The main issues included limited managerial capacity among local tourism managers, the absence of clear service standards, and weak coordination among local tourism stakeholders. This program aimed to strengthen institutional capacity, improve the quality of visitor services, and promote more participatory and sustainable destination governance. The program applied a participatory approach consisting of problem identification, joint planning, training on tourism service management, development of basic service standards, and field mentoring. The beneficiaries were local tourism management groups and community members directly involved in tourism services at Bahtera Beach. The results indicate improved understanding among managers regarding structured organizational governance and service management. Clearer task distribution, the implementation of basic service standards for visitors, and increased awareness of cleanliness and visitor comfort were observed as tangible improvements. In addition, the emergence of local leaders who actively coordinate service activities and support program sustainability became an important outcome. Overall, this program contributed to strengthening institutional capacity and enhancing the quality of the tourism experience at Bahtera Beach.